Co-location of Tidal and Offshore Wind Energy Generation: Hydrodynamic Analysis of Monopile Impact on Tidal Energy Resource (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Optimum and effective use of available marine space is necessary to benefit from ocean’s resources while limiting our impact to its environment. One idea is co-locating tidal energy generation devices with offshore wind turbines. For a realistic assessment of the resource potential and optimum placement of the tidal devices, interaction between the offshore wind turbine monopiles and tidal energy generation devices are needed.  This study investigates the impact of monopiles on the tidal resource within the wind farms, utilizing the existing monopiles as structural anchors for tidal energy converters.To address this, we conducted hydrodynamic modeling using TELEMAC-2D to assess the impact of monopiles on the flow patterns. In this model, flow is modelled as a two-dimensional depth-averaged incompressible fluid whereas the monopiles were modelled as point sources of drag (added momentum source estimated by the drag force generated by various monopile diameters). Two scenarios were simulated: one without monopiles and one with monopiles. By comparing the results of these scenarios, we created difference maps that reveal changes in flow velocity due to the presence of monopiles. Statistical parameters, such as average and maximum velocity, were calculated to quantify these impacts. These simulations were done for the Belgium Offshore wind zone in the North Sea which is one of the most densely populated offshore wind regions.Our findings show that monopiles influence the local hydrodynamics, with the highest impacts observed within the wind farm zones with denser monopile arrangement as expected. In contrast, zones between some wind farms exhibited flow acceleration, suggesting potential locations for tidal energy converters. This pattern was less evident in other inter-farm areas, and was not always linked to the distance between the monopiles.The study demonstrates the importance of site-specific hydrodynamic analysis to optimize the placement of tidal energy devices in offshore wind farm regions. By identifying zones with minimal disturbance and favorable flow conditions, our methodology contributes to the efficient integration of tidal and wind energy systems.